Avfallskampanjers påverkan på konsumenters beteenden - Magnusdotter,Sigrid (2020)
Although waste prevention is the top step in the Swedish waste hierarchy, many consumers prioritize recycling over waste prevention. This study examines if there is a connection between how much national organisations spend on information campaigns about waste prevention and about recycling with how consumers choose to act. In this research, more ongoing campaigns about waste prevention were found than campaigns about recycling. Research shows that it usually takes time to change behaviours through information campaigns, and information campaigns about waste prevention are a relatively new phenomenon. Campaigns about recycling have been around for longer, and this might be a reason why many consumers prioritize recycling over waste prevention. To be effective, information campaigns also need to be combined with other policy instruments such as taxes, deposite system, and city planning. More research is needed to ascertain if there is a connection between how consumers act on waste issues and recourses spent on information campaigns. Factors that might affect the outcome of an information campaign is how they interact with other campaigns and the ongoing public debate.
Keywords: Information campaigns; material recycling; waste hierarchy; waste minimization; waste prevention